APEX SCHOLAR PROGRAMME TO PRODUCE WORLDCLASS GRADUATES WITH SELF-IDENTITY FOR NATION BUILDING - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 28 September 2015 – Universiti Sains Malaysia (USM) is striving to enhance future talents in order to produce graduates who are able to embrace globalisation, are wellreceived and marketable in fulfilling global market demands through the APEX Scholar Programme, a collaborative effort between the Division of Students Affairs & Development and Alumni (HEPA) and the Centre for Academic Excellence & Student Advisory and Development (CDAE).